The Socialization of the Hellowork Program Manpower Service: Sosialisasi Program Hellowork Pada Dinas Tenaga Kerja - Al Rosyad, Adam; Usrotin Choiriyah, Ilmi (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to describe and analyze the Socialization of the Hellowork Program at the Pasuruan Regency Manpower Service. The research method used is descriptive qualitative. Data collection techniques through interviews, observation, and documentation with selected informants using purposive sampling technique. The results of the study on the Socialization of the Hellowork Program at the Manpower Office of Pasuruan Regency showed that the socialization of the program carried out by the Pasuruan Regency Manpower Office was good because it was carried out in various ways, but it was felt that it was not effective because there were still many Pasuruan residents who did not know about Hellowork. Since the Covid-19 pandemic, socialization has rarely been carried out because the budget has been refocused on Covid-19 aid funds.